Internationalisation of classroom: from higher education internationalisation strategy to practice - Romyen Kosaikanont (Penerbit Universiti Kebangsaan Malaysia, 2020)
Internationalisation is considered one of the crucial factors reshaping higher education in the 21st century to cope with multiple challenges. It is also widely recognised that internationalisation in higher education needs to take into consideration both the national and institutional contexts. Hence, it is fundamental that a higher education institution should derive its own definition, strategy, and strategic plan. This is to ensure full integration of internationalisation in its vision, operation and strategic planning of in its priorities in all dimensions. Often, mobility programmes especially outbound mobility students are perceived as important because mobile students acquire international, intercultural and global knowledge and skills. However, only 2.3 percent of the enrolled students the higher education level worldwide can participate in outbound mobility programmes. This paper draws on the author’s experience as a former vice president of a Thai public autonomous university in charge of internationalisation and a Thai native lecturer offering a course in “Thai Economy” in the Bachelor of Economics Programme. The paper argues that internationalisation of the classroom is crucial, and with carefully crafted course content, objectives, expected learning outcomes, activities and maximisation of the use of inbound mobility student, assessment and reflection can fill the gap in equipping non-mobile students with international, intercultural and global knowledge.